2012
DOI: 10.1002/ange.201203780
|View full text |Cite
|
Sign up to set email alerts
|

Ceria Nanoparticles that can Protect against Ischemic Stroke

Abstract: Einheitliche 3 nm große Cerdioxidnanopartikel können vor ischämischen Hirninfarkten schützen, indem sie reaktive Sauerstoffspezies (ROS) abfangen und die Apoptose zurückdrängen. PEGylierte Cerdioxidnanopartikel waren in vitro gegen ROS‐induzierten Zelltod wirksam. Optimale Dosen solcher Nanopartikel verringerten das Infarktvolumen und verlangsamten den ischämischen Zelltod.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 31 publications
1
67
0
Order By: Relevance
“…An increase in the population of Annexin V þ and PI þ cells was observed at higher dose of QCA. It is well known that ROS production and apoptosis are closely related and activation of caspase-3 is one of hallmark consequences of GSH depletion 35,36 . Therefore, the superior apoptosis-inducing potential of QCA is attributed to the combined effects of GSH-depleting QM and ROS-generating cinnamaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the population of Annexin V þ and PI þ cells was observed at higher dose of QCA. It is well known that ROS production and apoptosis are closely related and activation of caspase-3 is one of hallmark consequences of GSH depletion 35,36 . Therefore, the superior apoptosis-inducing potential of QCA is attributed to the combined effects of GSH-depleting QM and ROS-generating cinnamaldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Values listed under blots represent relative ratios of p-DRP1 S616 to total DRP1 protein normalized to actin nanoparticles to cross the BBB strikingly increased after injury (resulting in increased ROS/RNS). 57,58 By contrast, another study reported very small (2.9 nm diameter), citrate/ EDTA-stabilized CeO 2 nanoparticles administered intravenously to healthy rats appeared to cross the intact BBB, 56 suggesting that particle modifications might help improve neuronal delivery. In sum, considering the variability in findings to date, efficient delivery of nanoceria to neurons remains an important issue requiring further research and investigation.…”
Section: Discussionmentioning
confidence: 98%
“…[56][57][58] In two of these studies, CeO 2 nanoparticles were administered intravenously and the concentration of nanoparticles was very low in the normal brain. 57,58 The study by Kim et al 57 used nanoceria that were surface modified with an artificial polymer phospholipid-polyethylene glycol, which is often added to nanoparticles to improve uptake and biodistribution, 59 yet these particles were also found only in low amounts in brain tissue. However, the ability of (a) Western blots of p-DRP1 S616, total DRP1 and actin protein levels from neurons exposed for 3 h to aged SNOC (100 mM), nanoceria (100 nM; 3 h pretreatment) or fresh SNOC (100 mM) alone or a combination of nanoceria (100 nM) and fresh SNOC (100 mM).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 91 reported that CeONP can protect against ischemic stroke. Cerebral ischemia, or stroke, caused by a reduction of blood flow to the brain because of a clot or hemorrhage is the third leading cause of death worldwide.…”
Section: Cerium Oxide Nanoparticle C Xu and X Qumentioning
confidence: 99%